1997
DOI: 10.3168/jds.s0022-0302(97)75936-8
|View full text |Cite
|
Sign up to set email alerts
|

Response of Dairy Cows Treated with Bovine Somatotropin to a Luteolytic Dose of Prostaglandin F2

Abstract: The objective of this study was to evaluate the timing of follicular waves in cows treated with bovine somatotropin (bST) by measuring ovarian responses to a luteolytic dose of PGF 2 alpha on d 12 of the estrous cycle. Thirty lactating cows (26 Holstein and 4 Guernsey) were assigned to receive bST (500 mg; n = 18) or saline (control; 1.5 ml; n = 12) every 14 d for three injection cycles. On d 12 of a synchronized estrous cycle, cows were injected with PGF 2 alpha to induce luteolysis. Following PGF 2 alpha, 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 28 publications
0
20
0
2
Order By: Relevance
“…Cattle in negative energy balance typically have increased concentrations of GH (Armstrong et al, 1993;Bossis et al, 1999) due to decreased hepatic binding of GH (Keisler and Lucy, 1996). Reduction of the number of mounts received during estrus in bST-treated cows in the current experiment may be an evolutionary mechanism that decreases reproduction in undernourished cows (Kirby et al, 1997b).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Cattle in negative energy balance typically have increased concentrations of GH (Armstrong et al, 1993;Bossis et al, 1999) due to decreased hepatic binding of GH (Keisler and Lucy, 1996). Reduction of the number of mounts received during estrus in bST-treated cows in the current experiment may be an evolutionary mechanism that decreases reproduction in undernourished cows (Kirby et al, 1997b).…”
Section: Discussionmentioning
confidence: 72%
“…Estrous detection rate decreased linearly as concentration of bST administered to primiparous dairy cows increased (Morbeck et al, 1991), and multiparous dairy cows treated with bST had increased behavioral anestrus (Esteban et al, 1994). Further, Kirby et al (1997b) reported an increased inci-dence of undetectable estrus in dairy cows treated with bST; however, ovulation rate was not altered by bST. In the current study, duration of estrus, as well as number of mounts received, tended to be inversely correlated with concentrations of GH before the breeding season.…”
Section: Discussionmentioning
confidence: 95%
“…Serum progesterone concentrations were quantified by radioimmunoassay with a Coat‐a‐Count RIA kit (Diagnostic Products Corporation, Los Angeles, CA), as described previously by Kirby, Wilson, and Lucy (). Intra‐assay coefficients of variations were 4.82%, and the assay sensitivity was 0.08 ng/ml for the progesterone assay.…”
Section: Methodsmentioning
confidence: 99%
“…Serum progesterone concentrations were quantified by radioimmunoassay with a Coat-a-Count RIA kit (Diagnostic Products Corporation, Los Angeles, CA), as described previously by Kirby, Wilson, and Lucy (1997…”
Section: Progesterone Assaysmentioning
confidence: 99%
“…Entretanto, pesquisadores brasileiros como BURATINI JR et al (2000) verificaram aumento significativo no número de folículos recrutados na segunda onda, atribuindo este aumento à somatotropina, aumento este que pode estar relacionado ao aumento da concentração plasmática de IGF-I como encontrado por GONG et al (1991), GONG et al (1993), LUCY et al (1993), HERRLER et al (1994, DE LA SOTA et al (1996), KIRBY et al (1997), os quais obtiveram os mesmos resultados, relacionando nesse contexto a IGF-I, implicada no mecanismo do crescimento folicular.…”
Section: Discussionunclassified